Spirituality, crisis, and illusions - Losoncz Alpár (Belvedere Meridionale, 2014)
This article deals with the structural interpretations of the ongoing crisis. The author considers the approaches of Joseph Alois Schumpeter and Tibor Scitovsky that thematize the long-run destiny of capitalism. The viewpoint is constituted as the relation between the structural socio-economic tendencies and existential constellations. What is addressed by the crisis is capitalism as a dependent system. The author emphasizes that capitalism cannot survive without the outside sphere, reciprocal interactions, economics of community, eco-system and complex eco-social moments. This can be applied to the frequently mentioned embeddedness which is related to Polanyi and other researchers who are influenced by Polanyi’s concepts. Embeddedness can be analyzed through the holon, from the inside perspective. Only comprehensive perspective enables to see the entire horizon, since capitalism cannot summarize the eco-system, not even with the most sophisticated techniques that recognize monetary expressions.